Socioeconomic and living condition challenges for urban slums in Lagos, Nigeria - Ifeoma, Obilaonu Jane (2022)
Lagos is reportedly one of the Nigerian states with the highest number of slums who are experiencing housing challenges. Urban slums dwellers in Lagos are vulnerable parts of the society that are facing various types of problems like health and hygiene related problems, low level of income, due to poor housing conditions and other serious housing challenge. The rate at which urban slums are increasing in the state has become worrisome as it has continued unabated despite several attempts, by the Lagos state government to checkmate the phenomenon. There is need to develop the plans and policies for the upgradation of the slum dwellers in terms of infrastructural development and basic amenities. Unfortunately, the slums are presently faced with so many consequences due to many factors among which is their socioeconomic conditions. Understanding their socioeconomic conditions will help the government in designing a better framework for the development and upgradation of the slums. Therefore, in this study, the socioeconomic conditions of Lagos urban slum dwellers are investigated and analysed. To achieve this, a quantitative research approach was used, and the survey method was used in obtaining data from the study respondents. Convenience sampling technique was used to obtain data from a sample of 384 using a structured questionnaire. The sample of the study was drawn from six slums areas in Lagos State. Findings of the study revealed that the socioeconomic status of the urban slum dwellers that participated in this study is low, with an average yearly income which is below the poverty line, low yearly rent, and types of houses they live in. The findings also showed that, despite the low socioeconomic status of the dwellers, they demonstrated resilience in every aspect. Lastly, it was also found that perceived factors that influence urban slum expansion include, economic (availability of cheaper areas for micro businesses), socioeconomic (search of employment opportunities), and social reasons (social affinity and family).